2007
DOI: 10.1128/jvi.00348-07
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements of NS4A for Internal NS3 Cleavage and Polyprotein Processing of Hepatitis C Virus

Abstract: The NS3 protein of hepatitis C virus (HCV) possesses protease activity responsible for the proteolytic cleavage of the viral polyprotein at the junctions of nonstructural proteins downstream of NS3. The NS3 protein was also found to be internally cleaved. In this study, we demonstrated that internal cleavages occurred on the NS3 protein of genotype 1b in the presence of NS4A, both in culture cells and with a mouse model system. No internal cleavage products were detected with the NS3 and NS4A proteins of genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In either case, internal cleavages occur within the helicase domain of NS3 and yield C-terminally truncated molecules. While a single study suggested that cellular proteases mediate the internal NS3 cleavage in HCV (36), it was demonstrated that an autocatalytic protease activity of NS2B/ NS3 or NS3/NS4A is responsible for internal NS3 processing (9,13,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, internal cleavages occur within the helicase domain of NS3 and yield C-terminally truncated molecules. While a single study suggested that cellular proteases mediate the internal NS3 cleavage in HCV (36), it was demonstrated that an autocatalytic protease activity of NS2B/ NS3 or NS3/NS4A is responsible for internal NS3 processing (9,13,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…As such, proteolytically active single-chain NS4A3 constructs of HCV have been engineered for bacterial expression, representing N-terminal fusions of a central segment of NS4A with NS3 via a short linker sequence (11,12). For HCV, an intramolecular processing of NS3 has been reported that occurs within the helicase domain (13).…”
Section: Lassical Swine Fever Virus (Csfv) Is the Causative Agent Omentioning
confidence: 99%
“…Our earlier finding that the internal NS3 cleavage can occur in trans suggested the existence of intermolecular interactions of NS3 proteins [1]. Previous structural analysis also suggested the formation of NS3 helicase dimer [7].…”
Section: Resultsmentioning
confidence: 83%
“…Since the NS4A I25 residue is important, as part of the NS4A central region for enhancing the NS3 protease activity, this residue has been related in experimental models with autoprocessing of NS3 (Butkiewicz et al 1996;Kou et al 2007;Hou et al 2009). In this report, we determined two NS4A variants with I25C substitution from blood donors infected with HCV; the analysis of these NS4A variants suggests that a mutation in I25 affects the protease activity of NS3.…”
Section: Discussionmentioning
confidence: 99%
“…This linker makes NS4A able to interact with NS3 through a beta-turn as in the natural full-length NS3 (1-631) -NS4A complex. The single-chain protein (NS4A (21-32) -GSGS-NS3 (3-181) ) expressed in Escherichia coli shows enzymatic parameters equivalent to those of the wild type NS3 (1-631) -NS4A protein generated in eukaryotic cells and can be over expressed to high levels as a soluble protein (Dimasi et al 1998;Taremi et al 1998;Howe et al 1999;Leyssen et al 2000;Wang et al 2004;Kou et al 2007). In this study we identified, by DNA sequencing of the 4870-5902 nucleotide region, NS4A amino acid variants from serum samples of HCV infected patients; moreover, we performed amino acid modifications on the 21-32 NS4A sequence in order to understand better the role of NS4 as regulator in HCV replication.…”
mentioning
confidence: 99%